Association between immunization coverage and atopy in children with or without family history of atopic disease - Isabella Riandani; Budi Setiabudiawan; Cissy B. Kartasasmita (Indonesian Pediatric Society, 2008)
Background Atopic diseases are determined by the interactionbetween genetic and environmental factors. The possible effectsof immunization, as one of environmental factors, on atopy remaina matter of controversy.Objective We conducted an observational clinical epidemiologyto find out the protective effect of high vaccination coverage toatopy in children.Methods During January through March 2006, 150 of749 childrenat Garuda, Padasuka, and Babakan Sari Primary Health Care inBandung were randomized from group with and without familyhistory of atopic disease. Atopy derived from skin prick test andtotal serum lgE was evaluated. Atopy was defined as a positiveskin test to any of the eight allergens tested. The immunizationswere recorded from Kartu Menuju Sehat (KMS). Statistical analysesincluded Chi square to compare prevalence, independent T-testand Mann-Whitney to compare mean.Results Atopy was found in 28.2% of284 subjects, of which 32.4%with and 23.9% without a family history of atopic disease. Themedian of total serum lgE level was higher in children with familyhistory of atopic disease and in atopy children. Children weregrouped according to total dose of basic immunizations (0-17 and2: 18) based on Program Pengembangan Imunisasi (PPI). There wasnonsignificant association between total doses of immunizationand atopy. Even though no statistically significant, the cumulativeimmunization doses were inversely related to the median of totalserum IgE level.Conclusions The immunization coverage has not decreased atopyrisk.